Optimization of preparation and analysis of Paraffin/SiO2 composite PCMs via sol-gel method. Issue 3 (March 2019) - Hu, Min; Yan, Zibo; Peng, Li; Guo, Na; Liu, Zhongwei
Abstract: Using the economical and environmental paraffin as core, Paraffin/SiO2 composite phase change materials (PCMs) were prepared by sol-gel method. Industrial water glass for preparation of the nano-SiO2 was served as a shell with the modification of silane coupling agent. We combined Soxhlet extraction with penetration circle for the coating rate and the optimization of preparation was obtained via SPSS. The composite PCMs were investigated by SEM, TG, FT-IR, DSC technique. The results indicated that the optimization of preparation(PH = 4.5 and T = 35°C) was available. When the efficient coating rate of paraffin reached up to 60.04%, the phase-transition temperature was 38.73°C and the enthalpy of phase change was 72.88J/g. Moreover, thermal stability and reliability of the paraffin/SiO2 composite PCMs were proved through TG curves. So it could be formulated that paraffin/SiO2 composite PCMs with no leakage, excellent thermal storage capacity could be employed in energy conservation as a kind of thermal functional material.